Rapid spatial growth of cities and its planning implications for developing countries: a case study of Abuja, Nigeria. - Gladys Ogochukwu Chukwurah; Chioma onwuneme John-nsa; Francis Okeke; Eze Charles Chukwudi; Isimah Matthew Ogorchukwu (Faculty of Geography, Universitas Gadjah Mada, 2022)
Accelerated spatial growth of urban areas is a key driver to land use/land cover change with its concomitant effect on environmental sustainability. The dearth of data on the rate of urban expansion, especially in many developing countries, including Nigeria has continued to hinder effective land use planning and sustainable development. The study aims to identify and analyze the settlement patterns and trends in urban growth at ten years intervals and their planning implications in Abuja, Nigeria. It relied on data generated via remote sensing and Geographic Information Systems to create the map and examine the land cover change in the study area. Classification of land cover using LANDSAT data and land cover transitions for 29 years (1990 to 2019) were mapped and the net land cover change was computed. The results showed the settlement pattern and an increase in the urban built-up area ranging from 1.8% in 1990 to 19.3% in 2019. The dispersion pattern revealed a large concentration of the built-up spaces to be in the eastern region and that the expansion continued from east to south and south-west. The bare land cover types were found to have increased while vegetation land cover decreased rapidly by 30.4% from 1990-2019. The study recommends the need for city planners to decentralize urban planning and development control with adequate provision of affordable urban facilities at the peripheries of cities in Nigeria. Furthermore, massive integration of green infrastructure in built-up areas is required to mitigate the effects of vegetation loss in cities.